Comparison of Long-Term Outcomes After Percutaneous Coronary Intervention in Patients With Insulin-Treated Versus Non-Insulin Treated Diabetes Mellitus - Biswas, S.; Dinh, D.; Andrianopoulos, N.; Lefkovits, J.; Ajani, A.; Duffy, S.J.; Chan, W.; Walton, A.; Brennan, A.; Clark, D.J.; Hiew, C.; Oqueli, E.; et al. (EXCERPTA MEDICA INC-ELSEVIER SCIENCE INC, 2021)
There are conflicting data on whether patients with insulin-treated diabetes mellitus (ITDM) have poorer outcomes compared with non-insulin treated diabetic (non-ITDM) patients following percutaneous coronary intervention (PCI). We therefore compared clinical outcomes following PCI in ITDM versus non-ITDM patients. We prospectively collected data on 4,579 patients with diabetes underwent PCI between 2005 and 2014 in a large multicenter registry and dichotomized them as having ITDM (n = 1,111) or non-ITDM (n = 3,468). The non-ITDM group was further divided into diet control only (diet-DM; n = 786) and those taking oral hypoglycemic agents (OHG-DM; n = 2,639), and clinical outcomes were compared with ITDM patients. Median follow-up for long-term mortality was 4.2 years (IQR 2.0 to 6.6 years). ITDM patients were more likely to be female, obese, and have severe renal impairment (all p <0.001). Procedural characteristics were similar other than a greater use of drug-eluting stents in ITDM patients. On multivariable analysis, ITDM was an independent predictor of 12-month major adverse cardiovascular and cerebrovascular events (MACCE; OR 1.26, 95% CI 1.02 to1.55, p = 0.03). Dividing the non-ITDM group further by treatment, a progressively higher rate of 12-month MACCE across the 3 groups was observed (13.5% vs 17.9% vs 21.8%; p <0.001). Long-term mortality was similar in the diet-DM and OHG-DM groups, but significantly higher in the ITDM group on Kaplan-Meier analysis (log-rank p <0.001). In conclusion, there is a clear gradient of adverse outcomes with escalation of therapy from diet control to OHGs to insulin.